Interventional Treatment for Portal Venous Occlusion After Liver Transplantation. Issue 4 (January 2015) - Wang, Jianfeng; Yang, Weili; Huang, Qiang; Gao, Kun; Wei, Baojie; Zhai, Renyou; Shi, Yaoping; Mohammad Ali Abd Elrazek., Abd Elrazek
<x xml:space="preserve">Abstract</x> Abstract Portal vein (PV) occlusion after liver transplant is an uncommon clinical situation, and percutaneous interventional treatment for this condition has not been widely described. The aim of this study was to evaluate the long-term treatment effect of interventional treatment for PV occlusion after liver transplantation (LT). Follow-up data of 13 patients who received interventional treatment for PV occlusion after LT between July 2007 and April 2013 were analyzed. Of these, 10 patients had portal hypertension-related signs and symptoms. Percutaneous balloon angioplasty and stent placement were performed, with percutaneous thrombolysis treatment as appropriate. Embolization therapy was required for significant collateral circulation. Technical and clinical success, complications, and patency of PV were analyzed. Both technical and clinical success was achieved in 11 of the 13 patients (84.6%). Direct portogram showed limited PV occlusion in 7 patients and extensive PV occlusion in 4 patients. The former underwent balloon angioplasty followed by stent placement, while the latter underwent balloon angioplasty followed by stent placement and additional percutaneous thrombolysis treatment. Embolization therapy for collateral circulation was performed in all 4 patients with extensive PV occlusion and 1 patient with limited PV occlusion. All stents remained patency during the follow-up (28.5 ± 6.8 months). No portal hypertension-related symptoms reoccurred during follow-up. In conclusion, interventional treatment for PV occlusion after LT showed a high success rate and good long-term results. Comprehensive interventional treatment should be used for extensive PV occlusion.